Teknik Penanganan Masalah Penyidikan Kepolisian pada Satuan Reserse Kriminal Kepolisian Resor Kota Bulungan Kalimantan Utara (Studi Kasus Pembunuhan Korban Lansia di Panti Sosial Tresna Wherda) - Gultom, Brian Daven Kyher; Joko Widarto; Markoni; Nardiman (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This study aims to analyze the problems faced by the Criminal Investigation Unit of the Bulungan Police Resort in North Kalimantan in handling murder cases involving elderly people in social care facilities. This study also aims to propose solutions and techniques to deal with these investigative problems. This study discusses the challenges faced by the Bulungan City Police Resort criminal investigation unit in handling murder cases involving elderly victims. This emphasizes the importance of quality training for investigators to effectively address the complexity of such cases. Data collection methods included document analysis and interviews. The data analysis method used is qualitative descriptive analysis. This study highlights the challenges faced by the criminal investigation unit in handling murder cases involving elderly victims at the Bulungan City Police Resort. This research identifies difficulties in the management and use of evidence in criminal investigations, including challenges in collecting and examining evidence at crime scenes. This study emphasizes the need for quality training for researchers to effectively address the complexity of such cases. The research analysis concluded that the investigation of violence against the elderly at the Tresna Wherda Social Home faces challenges such as limited evidence, complex cases, and possible mental disorders of the perpetrators. Handling violence against the elderly requires a holistic approach involving the police, health institutions, social workers, and the community as a whole